Interpretation of Low‐Temperature Thermochronometer Ages From Tilted Normal Fault Blocks. Issue 10 (15th October 2018) - Johnstone, S. A.; Colgan, J. P.
Abstract: Low‐temperature thermochronometry is widely used to measure the timing and rate of slip on normal faults. Rates are often derived from suites of footwall thermochronometer samples, but regression of age versus structural depth fails to account for the trajectories of samples during fault slip. We demonstrate that in rotating fault blocks, regression of age‐depth data is susceptible to significant errors (>10%) in the identification of the initiation and rate of faulting. Advection of heat and topographic growth influence the thermal histories of exhumed particles, but for a range of geologically reasonable fault geometries and rates these effects produce Apatite (U‐Th)/He ages comparable to those derived from rotation through fixed isotherms. We apply the fixed‐isotherm model to published data from the Pine Forest Range and the East Range, Nevada, by incorporating field and thermochronologic constraints into a Markov chain Monte Carlo model. Modeled parameters for the Pine Forest Range are described by narrow ranges of geologically reasonable values. Compared to slip rates of 0.3–0.8 km/Myr and an initiation of faulting ca. 11–12 Ma derived from visual inspection, the model predicts an average slip rate of 1.1 km/Myr and an onset of faulting ca. 9–10 Ma. For the East Range fault block the model suggests that faulting began 17 Ma with an extension rate of 3 km/Myr and slowed to an extension rate of 0.5 km/Myr at 14 Ma. The absence of a preserved partial retention zone in the East Range sample set limits how well the model can predict fault block geometry. Plain Language Summary: Normal faults form in settings where the crust is extending and can be associated with both seismic hazards and natural resource emplacement. To learn about the history of normal faults we often turn to minerals that record the history of cooling that occurs as fault slip carries rocks from depth to the relatively cool surface of the Earth. To interpret these cooling histories, it is common practice to treat the cooling of these minerals as resulting from the vertical translation of a series of samples through the crust. However, this ignores the basic geologic observation that sets of samples are often collected from areas that have undergone rotation as well as vertical translation. Here we investigate how this rotation may complicate the interpretations we make about fault histories by simulating the cooling histories of minerals that undergo faulting and associated rotation. We find that traditional methods for inferring slip histories on faults may be significantly biased and propose a relatively simple alternative for investigating these systems that is consistent with our geologic observations. Key Points: Curved particle trajectories in tilted normal fault blocks complicate the interpretation of thermochronometer ages Simple interpretation of age‐versus‐structural depth plots can significantly mispredict the onset and rate of faulting Two examples from the Basin and Range Province of Nevada reveal promise for quantitative inference of slip history from kinematic descriptions of sample paths